(untitled) (Journal of Health Sciences, 2012)
Introduction: One of the cognitive aspects of personality is intelligence. A large number of previous studies have shown that the intelligence within the criminal population is decreased, particularly in its verbal aspect.The aim of this study is to determine whether there is a link between intelligence and criminal behavior and how it is manifested.Methods: The research involved criminal inmates of the Correctional institutes of Republic of Srpska and Court Department of Psychiatry Clinic Sokolac who committed homicide and various non-homicide acts. Thetest group consisted of 60 inmates who have committed homicide (homicide offenders) and a control group of 60 inmates who did not commit homicide (non-homicide offenders). The study was controlled, transverse or cross-sectional study.Results: Average intelligence of inmates (homicidal and non-homicidal) was IQ 95.7. Intelligence of homicide inmates was IQ 97.4 and non-homicide IQ 94.09. Intelligence coeffi cients for non-homicide inmatesubgroups were as follows - subgroup consisting of robbery offenders (IQ 96.9), subgroup consisting of theft perpetrators (IQ 93.83), subgroups consisting of other criminal offenders (IQ 92.8). Verbal intellectual ability– IQw of homicide inmates was 91.22, and 91.10 IQw of non-homicide inmates. Intellectual abilities in nonverbal or manipulative part were average, but they were higher in homicide inmates group (IQm 103.65) than in the group of non-homicide inmates (IQm 97.08).Conclusion: Average intelligence of investigated inmates (homicide and non-homicide) is lower than in the general population and corresponds to low average. Verbal part of intelligence is lowered while nonverbalpart is within the average range.